Evaluating the efficacy and safety of different neoadjuvant immunotherapy combinations in locally advanced HNSCC: a systematic review and meta-analysis - Liu, Chang; Li, Mingzhu; Liu, Xiaojie; Shi, Ting; Wang, Yun; Sui, Chaoyang; Zhang, Wenan; Wang, Bowen (Frontiers in Immunology, 2024)
Background Immune checkpoint inhibitors have demonstrated promising therapeutic outcomes in recurrent/metastatic (R/M) Head and Neck Squamous Cell Carcinoma (HNSCC), prompting numerous clinical trials to investigate the safety and efficacy of this approach in neoadjuvant therapy. This systematic review aims to consolidate and analyze the findings from various clinical trials combining neoadjuvant immunotherapy for HNSCC, with the goal of identifying the most effective neoadjuvant immunotherapy regimen. Methods The system conducted searches across electronic databases including PubMed, Embase, the Cochrane Library and Web of science from their inception to July 1, 2024. The primary focus was on evaluating efficacy (particularly pathological complete response (pCR), major pathological response (MPR), and overall response rate (ORR)) and safety (primarily assessed by grade 3-4 treatment-related adverse reactions). Results A total of 1943 patients from 32 studies were analyzed. Combining neoadjuvant immunotherapy with chemotherapy or radiotherapy demonstrated superiority over neoadjuvant immunotherapy alone in terms of the MPR rate, while showing no statistically significant difference in the pCR rate. Furthermore, the combination of neoadjuvant immunotherapy with chemotherapy or radiotherapy exhibited a lower CR rate compared to neoadjuvant immunotherapy with radiotherapy alone, but a higher PR rate and SD rate. Apart from the neoadjuvant immunotherapy group in isolation, there were no statistically significant differences in grade ≥3 treatment-related adverse events (TRAEs) and immune-related adverse events (irAEs) among the other three combination therapy groups. Conclusion This systematic review and meta-analysis indicate that patients with locally advanced HNSCC might benefit from neoadjuvant immunotherapy, particularly when used in conjunction with chemotherapy or radiotherapy. Nonetheless, additional data is required to definitively confirm its efficacy. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=553753, identifier CRD42024553753.